Choosing PLS path modeling as analytical method in European management research: A realist perspective. Issue 6 (December 2016) - Rigdon, Edward E.
Abstract: Today, there is heightened controversy about the value of partial least squares (PLS) path modeling as a quantitative research method, including within the domain of European management research. Critical lines of argument within the management and psychology literature assert that there is no reason to use PLS path modeling at all. At the same time, authors using PLS path modeling continue to advance fallacious arguments to justify their choice of method. This paper identifies flaws on both sides—invalid arguments in favor of using PLS path modeling and invalid arguments opposing its use—within the context of a unifying framework and a realist philosophy of science.